The Effectiveness of Positive Parenting Program (Triple-P) Training on Interaction of Mother-child with Intellectual Disability - Ma'soumeh Pourmohammadreza-Tajrishi; Mohammad A'shouri; Gholam Ali Afrouz; Ali Akbar Arjmand-nia; Bagher Ghobari-Bonab (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: Intellectual disability affects all aspect of individual's life, while use of parenting educational programs has been associated with strong outcomes. The aim of the present research was to determine of the effectiveness of positive parenting program (Triple-P) training on interaction of mother-child with intellectual disability. Materials & Methods: The present research was a quasi-experimental study by pre-test, post-test design with control group. Participants in this study were 40 mothers of students with intellectual disability. The samples were recruited through random clustering method from exceptional schools of Tehran provinces. Participants were divided into two groups (experimental and control group), each of which was consisted of 20 individuals. Experimental group received Triple-P in 10 sessions while control group did not. The instrument of present research was parent child relationship scale (PCRS) of Piyanta (1994). The obtained data were statistically analyzed by MANCOVA using SPSS software. Results: Findings showed that experimental and control groups had significant difference, At least in one of sub scales of the PCRS (P<0/001). The final results of MANCOVA showed that Triple-P had significant and positive effect on the conflict, closeness, dependency, and positive relationship (P<0/001).  Conclusion: The results indicated that Triple-P training has led to the improvement of interaction of mother-child with intellectual disability. It is suggested that specialists with implementation of Triple-P training promoted interaction of mother-child with intellectual disability.